Respostas

2014-08-14T11:12:41-03:00
Oi Victor.

Dada a equação:

\frac { 25^{ x }+125 }{ 6 } =5^{ x+1 }

\frac { (5^{ 2 })^{ x }+125=5^{ x }*5^{ 1 } }{ 6 }

\frac { 5^{ 2x }+125=5^{ x }*5 }{ 6 }

Fazendo a mudança de variável:

5^{ x }=y

\frac { y^{ 2 }+125=5y }{ 6 }

\frac { y^{ 2 }+125=30y }{ 6 }

y^{ 2 }-30y+125=0

Achando as raízes por SOMA e PRODUTO:

S=5+25\rightarrow 30\\ P=5*25\rightarrow 125

Agora é só trocar as raízes por Y.

5^{ x }=y\\ 5^{ x }=5\\ x=1\\ \\ 5^{ x }=y\\ 5^{ x }=25\\ 5^{ x }=5^{ 2 }\\ x=2\\ \\ S=\{ 1,2\}